Preparation of Investment Guidelines of the Thai and Foreign Elderly Housing Center Project, Nong Khai Province, Thailand - et. al., Acharaporn Seehawattana, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Living the end of life for the elderly is one of the important choices that the elderly makes in order to lead their lives based on their well-being. Appropriate accommodation will provide the elderly with a good quality of life. Therefore, this research aims to study the preparation of a guide to investment in the housing center project for the elderly, Thai and foreign in Nong Khai Province as the qualitative research. The instrument was Structure In-depth Interview to the targets for 50 persons by purposive sampling divided into four; (1) the first: 5 government officials involved in policy planning or action on the elderly according to government policy in Nong Khai Province. (2) the second 5 persons engaged in real estate or residential business. (3) The third: 20 Thai elderly. And (4) the fourth 20 elderly foreigners. Data analysis was done using Content Analysis. The results of the research showed that The Guidelines for Investment in the Housing Center Project for the Elderly, Thai and Foreigners, contains 15 important elements as follows: (1) Physical environment, (2) Utility service, (3) Medical services, (4) Legal measures or government policies, (5) Service after death, (6) Provincial potential, (7) Location of the accommodation center, (8) Atmosphere of the accommodation center, (9) Characteristics of the rooms in the accommodation center, (10) Accommodation center facilities, (11) Foodservice, (12) Activity, (13) Length of access to the accommodation center, (14) Ownership requirements, and (15) Reason for choosing.